Cognitive control over emotional information in current and remitted depression. (September 2020) - Quigley, Leanne; Wen, Alainna; Dobson, Keith S.
Abstract: Cognitive theories of depression propose that difficulty exerting cognitive control over emotional information may be involved in the development, maintenance, and/or recurrence of depression. This study evaluated depression-related biases in three cognitive control functions, namely inhibition, working memory updating, and set shifting. Currently depressed ( n  = 53), remitted depressed ( n  = 55), and non-clinical control ( n  = 51) participants completed computer-based paradigms designed to measure inhibition, working memory updating, and set shifting, respectively, involving emotional stimuli. As hypothesized, currently depressed participants exhibited biases in cognitive control over emotional information but did not exhibit broad impairments on a non-emotional measure of cognitive control. Specifically, currently depressed participants showed a reduced ability to inhibit the processing of negative distracting stimuli and to update working memory with emotional information, relative to control participants. Currently depressed participants also had greater difficulty shifting away from an emotion-relevant task set than from an emotion-irrelevant task set, whereas control participants did not show this bias. Remitted depressed participants did not demonstrate similar biases to currently depressed participants. Highlights: Currently depressed participants exhibited biases in cognitive control of emotional information. Currently depressed participants did not exhibit broad impairments on a non-emotional measure of cognitive control. Remitted depressed participants did not demonstrate similar cognitive control biases to currently depressed participants.